Introducing MRAC-PSS-VI to Increase Small-Signal Stability of the Power System after Wind Power Integration. (31st January 2022) - He, Ping; Zheng, Mingming; Jin, Haoran; Gong, Zhijie; Dong, Jie
Abstract : With the gradual increase of wind power penetration in the power system, the impact of wind farm on system stability is becoming more significant. This study designs the power system stabilizer (PSS) based on the model reference adaptive control (MRAC) method and virtual impedance (VI) control strategy. Then, the active power difference of the doubly fed induction generator (DFIG) is selected as input signal of MRAC-PSS-VI. The small-signal stability of the power system with the DFIG is enhanced by installing MRAC-PSS-VI on the rotor side control (RSC) control link. The controller model is built in DigSILENT/PowerFactory. The improvement effect of the controller on the low-frequency oscillation (LFO) characteristics of the power system is verified by using eigenvalue analysis and the time domain simulation method under different transmission powers of the tie line and different installed positions of the DFIG.